The Effects of Alexithymia on Self-Reflection and Insight in Major Depressive Disorder - Aysu Yakin Olgun; Meliha Zengin Eroglu (Haseki Tıp Bülteni)
Aim: We hypothesized that alexithymic depressive patients have low insight, which correlates with more severe depression and anxiety. In this context, we aimed to explore the correlation between insight and self-reflective abilities, alexithymia, as well as the presence and severity of major depression, which is the most diagnosed psychiatric disease in the world. Methods: We accepted 80 patients diagnosed with major depression who were in outpatient care at our psychiatry clinic between September and December 2020, along with 80 healthy controls. We applied the Toronto Alexithymia Scale (TAS-20), Hamilton Anxiety Rating Scale, Hamilton Depression Rating Scale, and Self-Reflection and Insight Scale (SRIS) to all participants. This study was designed as a cross-sectional observational study. Results: SRIS-insight score was found to be lower (p<0.001) in the patient group; higher scores were observed for difficulty in identifying feelings, difficulty in describing feelings, and the TAS-20 total score (p<0.001). TAS-20-total and subscales were found to be predicted by SRIS-insight in both groups (p<0.001; p<0.01). Conclusion: When clinicians evaluate alexithymic patients with major depression, they need to consider this alongside symptom evaluation, as these patients may have low insight.